Slow progression to AIDS in intravenous drug users infected with HIV in Norway. Issue 4 (August 1994) - Eskild, A; Magnus, P; Sohlberg, C; Kittelsen, P; Olving, J H; Teige, B; Skullerud, K
Abstract : STUDY OBJECTIVE--To study the rate of progression to AIDS and to death, and the causes of death among intravenous drug users in Norway. DESIGN--This was a prospective study. The study population was followed from diagnosis of HIV seropositivity until death or the end of the study period. The mean follow up was 56 months (range 1-73 months). SETTING--Subjects were recruited from a public HIV test clinic and followed by linkage to the National AIDS Registry and the National Cause of Death Registry. PARTICIPANTS--A total of 131 HIV positive intravenous drug users were included. The study population represented 75% of all intravenous drug users who had been diagnosed as HIV positive in Norway before 1987. None were lost to follow up. MAIN RESULTS--Four years after study entry, 3% (95% confidence interval, 0, 6%) had developed AIDS, while 15% (95% CI, 9, 21%) had died. Of the 25 subjects who died during the follow up period, 21 died from unnatural causes. Drug overdose accounted for 17 of these deaths. AIDS was the cause of death of three subjects only. Age more than 30 years at entry to the study was associated with short survival. CONCLUSIONS--These results suggest that the progression rate to AIDS in intravenous drug users is slow.